A Systematic Controller Design for a Photovoltaic Generator with Boost Converter Using Integral State Feedback Control - Labidi, Z. R.; Schulte, H.; Mami, A. (Engineering, Technology & Applied Science Research, 2019)
In this paper, a systematic controller design for a photovoltaic generator with boost converter using integral state feedback control is proposed. It is demonstrated that the state–space feedback enables the extraction of maximum available power under variable loads. For this purpose, a control-oriented state-space model of a photovoltaic array connected to a DC load by a boost converter is derived. This model is then linearized by one working point, but no further simplifications are made. The design-oriented model contains the dynamics of PV generator, boost converter, and the load. The controller design is based on the augmented model with an integral component. The controller is validated by a detailed plant model implemented in Simscape. The robustness of the controller with variable solar irradiation and DC load changes is demonstrated.